John G. Floyd papers - Floyd, John G. (John Gelston), 1806-1881.
Chiefly letters from John G. Floyd to his brother, Augustus, concerning legislative and political matters in Washington, D.C., and New York State. Also includes biographical sketches of Floyd and David Hubbard.
U.S. representative, jurist, and lawyer from New York.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Floyd, Augustus -- Correspondence; Hubbard, David, -- 1792-1874.; New York (State) -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1815-1861.; Jurists; Lawyers; Representatives, U.S. Congress -- New York (State)